Pupil dilation as an implicit measure of appetitive Pavlovian learning. (19th August 2019) - Pietrock, Charlotte; Ebrahimi, Claudia; Katthagen, Teresa M.; Koch, Stefan P.; Heinz, Andreas; Rothkirch, Marcus; Schlagenhauf, Florian
Abstract: Appetitive Pavlovian conditioning is a learning mechanism of fundamental biological and pathophysiological significance. Nonetheless, its exploration in humans remains sparse, which is partly attributed to the lack of an established psychophysiological parameter that aptly represents conditioned responding. This study evaluated pupil diameter and other ocular response measures (gaze dwelling time, blink duration and count) as indices of conditioning. Additionally, a learning model was used to infer participants' learning progress on the basis of their pupil dilation. Twenty‐nine healthy volunteers completed an appetitive differential delay conditioning paradigm with a primary reward, while the ocular response measures along with other psychophysiological (heart rate, electrodermal activity, postauricular and eyeblink reflex) and behavioral (ratings, contingency awareness) parameters were obtained to examine the relation among different measures. A significantly stronger increase in pupil diameter, longer gaze duration and shorter eyeblink duration was observed in response to the reward‐predicting cue compared to the control cue. The Pearce‐Hall attention model best predicted the trial‐by‐trial pupil diameter. This conditioned response was corroborated by a pronounced heart rate deceleration to the reward‐predicting cue, while no conditioning effect was observed in the electrodermal activity or startle responses. There was no discernible correlation between the psychophysiological response measures. These results highlight the potential value of ocular response measures as sensitive indices for representing appetitive conditioning. Abstract : Despite its central biological and pathophysiological significance, exploration of human appetitive Pavlovian conditioning remains sparse. This is commonly ascribed to the lack of a suitable measure that aptly reflects conditioned learning. In this study, we show that pupil diameter not only constitutes a sensitive and robust index for representing appetitive learning, but also precisely predicts individual trial‐by‐trial learning mechanisms in a Pearce‐Hall attention‐weighted learning model. Successful conditioning was confirmed by additional psychophysiological measures. These findings highlight the potential value of pupil diameter when exploring human appetitive conditioning and may help expedite research of this fundamental learning mechanism.